2020
DOI: 10.3390/nano10010145
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal Carbide Core/Shell Nanoparticles by Ultra-Short Laser Ablation in Liquid

Abstract: Transition metal carbide nanoparticles are a class of technological interesting materials with a wide range of applications. Among metal carbides, tantalum carbides have good compatibility with the biological environment while molybdenum carbides are used as catalyst in electrochemical reactions. Laser ablation of bulk transition metal targets in some liquids is here reported and laser ablation in organic solvents is used as simple synthetic strategy for the production of carbide nanostructures. Herein, the na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Regarding the multicomponent target, it is speculated that the non-congruent vaporization of ejected droplets is produced by short laser pulses, while ultrashort laser pulses have the propensity to highly retain the target stoichiometry. 168 In such case, ps-laser ablation to generate HEA NPs as discussed in Fig. 2e and f shows the well elemental homogeneity for even five elements used.…”
Section: Effect Of Lal Parameters On the Amorphization Of Carbide Nanoparticlesmentioning
confidence: 76%
“…Regarding the multicomponent target, it is speculated that the non-congruent vaporization of ejected droplets is produced by short laser pulses, while ultrashort laser pulses have the propensity to highly retain the target stoichiometry. 168 In such case, ps-laser ablation to generate HEA NPs as discussed in Fig. 2e and f shows the well elemental homogeneity for even five elements used.…”
Section: Effect Of Lal Parameters On the Amorphization Of Carbide Nanoparticlesmentioning
confidence: 76%
“…[20][21][22] However, due to the extreme conditions during the ablation process, the liquid decomposes and reacts with the ablated material. This Reactive Laser Ablation in Liquids (RLAL) has been reported in the past by chemical reactions such as oxidation of the target material [22][23][24] and carbonization [25][26][27] allowing alterations of the structural properties of the gained colloidal nanoparticles. This enables many opportunities [28][29][30] when developing new materials but also challenges when intending to tailor the material properties.…”
Section: Introductionmentioning
confidence: 99%
“…543 The importance of metal carbide interfaces for heterogeneous CO 2 hydrogenation catalysis in the activation of CO 2 was highlighted by Chen et al 330 Tantalum or molybdenum carbide core−shell nanoparticles were prepared by 800 nm, 100 fs pulsed laser ablation of Ta or Mo targets in water, ethanol, toluene, or acetone by Teghil et al 544 Acetone was more effective for making carbides, presumably due to the higher activity of ethanol decomposition products upon ablation, and the shorter plasma lifetime in femtosecond pulsed ablation reduced the risk of oxygen incorporation. 544 A series of metal carbides including TaC was found to catalyze the hydrogen evolution reaction. 545 Porosoff et al identified trends and descriptors for selective CO 2 conversion to CO over transition metal carbides in a careful comparative study.…”
Section: Carbidesmentioning
confidence: 99%
“…Tantalum or molybdenum carbide core–shell nanoparticles were prepared by 800 nm, 100 fs pulsed laser ablation of Ta or Mo targets in water, ethanol, toluene, or acetone by Teghil et al Acetone was more effective for making carbides, presumably due to the higher activity of ethanol decomposition products upon ablation, and the shorter plasma lifetime in femtosecond pulsed ablation reduced the risk of oxygen incorporation . A series of metal carbides including TaC was found to catalyze the hydrogen evolution reaction …”
Section: Outlook: Pulsed Laser In Liquids Made Nanomaterials As Poten...mentioning
confidence: 99%